A copper chelate selectively triggers apoptosis in myeloid-derived suppressor cells in a drug-resistant tumor model and enhances antitumor immune response. (April 2014) - Chakraborty, Paramita; Das, Satyajit; Banerjee, Kaushik; Sinha, Abhinaba; Roy, Susmita; Chatterjee, Mitali; Choudhuri, Soumitra Kumar
Abstract Myeloid-derived suppressor cells (MDSCs), one of the major orchestrators of immunosuppressive network are present in the tumor microenvironment suppress antitumor immunity by subverting Th1 response in tumor site and considered as a great obstacle for advancement of different cancer immunotherapeutic protocols. Till date, various pharmacological approaches have been explored to modulate the suppressive functions of MDSCs in vivo. The present study describes our endeavor to explore a possibility of eradicating MDSCs by the application of a copper chelate, namely copper N-(2-hydroxy acetophenone) glycinate (CuNG), previously found to be a potential immunomodulator that can elicit antitumorogenic Th1 response in doxorubicin-resistant EAC (EAC/Dox) bearing mice. Herein, we demonstrated that CuNG treatment could reduce Gr-1+CD11b+ MDSC accumulation in ascitic fluid and spleen of EAC/Dox tumor model. Furthermore, we found that CuNG mediated reduction in MDSCs is associated with induction of Th1 response and reduction in Treg cells. Moreover, we observed that CuNG could deplete MDSCs by inducing Fas-FasL mediated apoptotic cell death where death receptor Fas expression is enhanced in MDSCs and FasL is provided by activated T cells. However, MDSC expansion from bone marrow cells and their differentiation was not affected by CuNG. Altogether, these findings suggest that the immunomodulatory property of CuNG is attributed to, at least in part, by its selective cytotoxic action on MDSCs. So, this preclinical study unveils a new mechanism of regulating MDSC levels in drug-resistant cancer model and holds promise of translating the findings into clinical settings.